Understanding Gen Z’s Financial Management Behavior: The Mediating Role of Financial Self-Efficacy - Amelika, Aprilita Tri; Tubastuvi, Naelati; Suyoto; Rahmawati, Ika Yustina (Fakultas Ekonomi, Universitas Muslim Indonesia, 2026)
This study aims to analyze the mediating role of financial self-efficacy in the relationship between financial literacy, financial attitude, and lifestyle on financial management behavior of Generation Z in Purbalingga, Indonesia. A quantitative approach was used with primary data collection through a 5-point Likert-scale questionnaire, involving 226 respondents selected through purposive sampling. Data were analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) with SmartPLS version 4 software. The results of this study indicate that financial literacy, financial attitude, and lifestyle have a positive and significant effect on financial self-efficacy (p < 0.05). Furthermore, financial literacy, financial attitude, lifestyle, and financial self-efficacy have a positive and significant effect on financial management behavior (p < 0.05). The model's explanatory power is considered moderate, as reflected by the adjusted R2 values of 0.715 for financial management behavior and 0.518 for financial self-efficacy. Indirect analysis shows that financial self-efficacy mediates the influence of financial literacy, financial attitude, and lifestyle on financial management behavior. These findings contribute to the development of financial management behavior literature by emphasizing the importance of financial self-efficacy as a psychological mechanism that bridges the influence of financial factors and lifestyle on financial management behavior. Future research is recommended to explore other psychological or contextual factors that may influence financial management behavior.